Literary Spaces: Visions of Nature and Sense of Place in the Poetry of William Wordsworth and Claudio Rodríguez (Castilla. Estudios de Literatura, 2018)
In spite of being distant in both space and time, the works of the British poet William Wordsworth (1770-1850) and the Spanish poet Claudio Rodríguez (1934-1999) share some common elements; however, the main element linking them is their love of nature. The following paper will analyze, from an ecocritical stance, how these two poets understand nature and how they feel attached to her. No doubt this love of nature has its roots in childhood and this fact is clearly shown in the works of both poets. So, the aim of this article will be to compare both visions of nature and how nature is for them not only the place they love, but also the place they feel attached
Keywords: sense of place; Ecocriticism; nature; William Wordsworth